Enhanced malignant transformation induced by expression of a distinct protein domain of ribonucleotide reductase large subunit from herpes simplex virus type 2. - Ali, M A (1991)
The 1.3-kilobase (kb) Pst I DNA fragment C (Pst I-C) of herpes simplex virus type 2 (HSV-2) morphological transforming region III (mtrIII; map unit 0.562-0.570) encodes part of the N-terminal half of the large subunit of ribonucleotide reductase (RR1; amino acid residues 71-502) and induces the neoplastic transformation of immortalized cell lines. To assess directly the role of these RR1 protein sequences in cell transformation, the Pst I-C fragment was cloned in an expression vector (p91023) containing an adenovirus-simian virus 40 promoter-enhancer to generate recombinant plasmid p9-C. Expression of a protein domain (approximately 65 kDa) was observed in p9-C-transfected COS-7 and Rat2 cells but not in those transfected with plasmid pHC-14 (Pst I-C in a promoterless vector). In Rat2 cells, p9-C induced highly transformed foci at an elevated frequency compared with that of pHC-14. Introduction of translation termination (TAG) condons within the RR1 coding sequence and within all three reading frames inactivated RR1 protein expression from p9-C and reduced its transforming activity to the level seen with the standard pHC-14 construct. Wild-type p9-C specified a protein kinase capable of autophosphorylation. Computer-assisted analysis further revealed significant similarity between regions of mtrIII-specific RR1 and amino acid patterns conserved within the proinsulin precursor family and DNA transposition proteins. These results identify a distinct domain of the HSV-2 RR1 protein involved in the induction of enhanced malignant transformation. In addition, the data indicate that the mtrIII DNA itself can induce basal-level transformation in the absence of protein expression.